Structural and luminescence properties of borate glass with lithium and strontium modifier doped with transition metal ions - Wan, Ming Hua (Trans Tech Publications, 2012)
A system of borate based glass with different modifier but similar dopant was investigated to determine both the structural and photoluminescence properties. The glass sample from the series of X(M):(1-X)B 2O 3 where 0.2 ≤: X ≤:0.7 mole% and M was Li 2O and SrO, and the metaborate composition of glass was doped withMn 2+, Fe 2+ and Zn 2+ ions. The effect of the modifier towards the structural and photoluminescence properties in the glass samples was investigated using Fourier-Transfer Infrared (FT-IR) spectroscopy and photoluminescence spectroscopy. Infrared spectrum revealed the traces of BO 3 and BO 4 units at different modifier and concentration. Significant changes in the host structure showed modification at specific region depending on the type of modifier. The photoluminescence of the samples were studied using the luminescence spectrophotometer. The samples were excited at different emission wavelength to compare the results. This study showed that with the introduce Mn 2+, Fe 2+ and Zn 2+ ions as activators within the host material enhanced photoluminescence characteristic.